Pembelajaran E-Learning Berbasis Google Clasroom Berbantuan Vidio Youtube pada Materi Statistika untuk Meningkatkan Motivasi Belajar Siswa Kelas XII-IPS 4 SMAN 3 Selong - Juaini, Muhammad (Lembaga Yasin AlSys, 2023)
This Classroom Action Research aims to increase the motivation to study statistics for class XII IPS-4 SMAN 3 Selong through Google Classroom-based E-learning learning assisted by YouTube videos and describe the increase in learning motivation for class XII IPS-4 SMAN 3 Selong through Google-based E-Learning Classroom assisted by youtube videos. The condition of the Covid-19 pandemic requires implementing physical distancing so that face-to-face learning cannot be carried out and learning is forced to be carried out online (online) and student motivation is still low in learning mathematics. This research was conducted in two cycles of 30 students. Data collection techniques through observation and motivational questionnaires. The implementation of Google Classroom-based E-Learning assisted by YouTube videos is stated in very good, good, quite good, not good, and not good categories, while the motivation to learn mathematics is expressed in very high, high, medium, low and very low categories. Based on the results of the research conducted, it can be concluded as follows: 1) the implementation of Google Classroom-based E-Learning assisted by YouTube videos in cycle I was in the fairly good category and in cycle II in the good category. 2) Motivation to learn statistics material for class XII IPS-4 SMA Negeri 3 Selong in cycle I was low, cycle two was moderate, namely in cycle I the average motivation to learn mathematics was 66.3% while in cycle II it rose to 72.4% .